2015
DOI: 10.1016/j.jchb.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Admixture and genetic relationships of Mexican Mestizos regarding Latin American and Caribbean populations based on 13 CODIS-STRs

Abstract: Short tandem repeats (STRs) of the combined DNA index system (CODIS) are probably the most employed markers for human identification purposes. STR databases generated to interpret DNA profiles are also helpful for anthropological purposes. In this work,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 54 publications
(44 reference statements)
6
26
0
Order By: Relevance
“…Many groups have described the genetic background of the Mestizo population in Latin America (Martinez-Espin et al, 2006;Salazar-Flores et al, 2015). Recent studies show that STR analysis of the Guatemalan Mestizo population has revealed an elevated Amerindian ancestry.…”
Section: Guatemalan and Mayan Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Many groups have described the genetic background of the Mestizo population in Latin America (Martinez-Espin et al, 2006;Salazar-Flores et al, 2015). Recent studies show that STR analysis of the Guatemalan Mestizo population has revealed an elevated Amerindian ancestry.…”
Section: Guatemalan and Mayan Culturementioning
confidence: 99%
“…Recent studies show that STR analysis of the Guatemalan Mestizo population has revealed an elevated Amerindian ancestry. However, the ancestral pool used for these comparisons was comprised of Mexican Amerindians (Salazar-Flores et al, 2015).…”
Section: Guatemalan and Mayan Culturementioning
confidence: 99%
“…In brief, based on the PowerPlex 16 system, our results support a relative homogeneity among Mexican populations from the Central region, excluding the Western region from this cluster. This conclusion applies to Mestizos (admixed), who constitute the largest proportion of the Mexican population (~90%) (Rubi-Castellanos et al 2009;Salazar-Flores et al 2015), but is invalid for Native American groups, who display a particular genetic structure ). The genetic structure described herein is important in forensic casework because it allows geneticists using alternative STR population data, given that most of the Mexican populations do not have their own STR databases.…”
Section: Interpopulation Comparisonmentioning
confidence: 99%
“…In 2011, the federal State of Mexico (located within the Central region, Mexico) established a civil and criminal STR database containing approximately 2000 DNA profiles analyzed with the commercial PowerPlex 16 System (Krenke et al 2002). Although many Mexican populations have been analyzed with autosomal STRs to support forensic casework (Rubi-Castellanos et al 2009;Salazar-Flores et al 2015), only the following states/regions of the country have been studied with the PowerPlex 16 kit: Guanajuato, Veracruz, Nayarit, Yucatan, Mexico City, and the Western region (Rangel-Villalobos et al 2010;González-Herrera et al 2010;Ramírez-Flores et al 2014;Martínez-Sevilla et al 2016). Furthermore, the population structure and genetic relationships of the Mexican populations remain unexplored using PowerPlex 16 System.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted in Mexican-Mestizos to validate the application of autosomal short tandem repeats (STRs) for human identification purposes. 1,2 However, in Mexico, this forensic validation requires the study of different populations, given the genetic structure demonstrated among Mestizos from different regions. 3 Based on the 13 STRs of the Combined DNA Index System (CODIS), it has been claimed that the European ancestry increases gradually towards the Northwestern region and diminishes towards the Central and Southeastern regions; conversely, the Amerindian ancestry displays an opposite pattern increasing towards the Central and Southeastern region, and decreasing towards the Northwestern region.…”
Section: Introductionmentioning
confidence: 99%